Self-Assessed Severity as a Determinant of Coronavirus Disease 2019 Symptom Specificity: A Longitudinal Cohort Study. (13th February 2022) - Bershteyn, Anna; Dahl, Angela M; Dong, Tracy Q; Deming, Meagan E; Celum, Connie L; Chu, Helen Y; Kottkamp, Angelica C; Greninger, Alexander L; Hoffman, Risa M; Jerome, Keith R; Johnston, Christine M; Kissinger, Patricia J; et al.
Abstract: Coronavirus disease 2019 symptom definitions rarely include symptom severity. We collected daily nasal swab samples and symptom diaries from contacts of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) case patients. Requiring ≥1 moderate or severe symptom reduced sensitivity to predict SARS-CoV-2 shedding from 60.0% (95% confidence interval [CI], 52.9%−66.7%) to 31.5% (95% CI, 25.7%− 38.0%) but increased specificity from 77.5% (95% CI, 75.3%−79.5%) to 93.8% (95% CI, 92.7%−94.8%).